2013
DOI: 10.1007/s40258-013-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Systematic Review of Budget Impact Analyses on Drugs in the EU Countries

Abstract: Our review confirmed that the BIA is not yet a well-established technique in the literature and many published studies still fail to reach an acceptable quality. In particular, BIAs funded by pharmaceutical companies appear to be tailored to show short-term savings induced by new, highly priced products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 25 publications
4
51
0
3
Order By: Relevance
“…A summary of recommended design and common design flaws identified in this review is presented in Table 4. The finding of variability in the inclusion of key design elements was also made in the previous reviews of budget-impact analyses, including the review by Orlewska and Gulácsi [20] and the recent review of budget-impact analyses for European Union countries by van de Vooren et al [21]. Our review has provided additional details about deviations from recommended practice for each of the seven key elements.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…A summary of recommended design and common design flaws identified in this review is presented in Table 4. The finding of variability in the inclusion of key design elements was also made in the previous reviews of budget-impact analyses, including the review by Orlewska and Gulácsi [20] and the recent review of budget-impact analyses for European Union countries by van de Vooren et al [21]. Our review has provided additional details about deviations from recommended practice for each of the seven key elements.…”
Section: Discussionsupporting
confidence: 64%
“…All previous reviews of budget-impact models have presented information on model design and have concluded that it is variable [19][20][21]. As found in this review, this variability persists.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations